Digital Transformation Strategy providing drivers, prioritization, and an assertive planning: an Experience Report of a Business Conglomerate - Carturan, Sara B. O. G.; Rezende, Elaine; Goya, Denise H. (Anais Estendidos do Congresso Brasileiro de Software: Teoria e Prática (CBSoft), 2022)
During the development of a Digital Transformation (DT) Strategic Plan, it should be considered Business drivers, management models, recognized IT methodologies, IT processes and technical/business dimensions. However, human value is so important as the plan because behavioral issues and conflicts of interest could limit or destroy the plan. This paper also discusses project phases and what were the main points emerged. The project enabled discussions and the engagement of IT leaders, respecting points of view and defining priority actions that were materialized in initiatives in DT Strategic Plan. In addition, it was necessary to re-design IT organizational structure with roles and responsibilities to support DT Strategic Plan.